Sensory Experience and Religious Perception: Accounts of Faith in Visually Impaired People - Mariya Slavcheva (Journal of Folklore and Popular Culture)
This paper examines the relationship between blindness and belief in divine intervention among visually impaired individuals. Drawing on mythological, folkloric, and biblical contexts, it explores how sensory experiences, apart from sight, influence their faith narratives. Through social anthropological methods and extensive fieldwork, the study addresses key questions about the spontaneous emergence of religious themes, the transformation of these beliefs in the works of blind authors, and their role in coping with daily challenges. The analysis highlights how sensory experiences enhance faith and shape self-perception, motivating the visually impaired in their everyday lives.